2020
DOI: 10.14814/phy2.14366
|View full text |Cite
|
Sign up to set email alerts
|

Thermal distribution, physiological effects and toxicities of extracorporeally induced whole‐body hyperthermia in a pig model

Abstract: Background Extracorporeally induced whole‐body hyperthermia (eWBH) might be a beneficial treatment in cancer patients. Objectives of this pig study were to assess thermal distribution, (patho‐)physiological effects, and safety of eWBH with a new WBH device. Methods Fourteen healthy adult pigs were anesthetized, mechanically ventilated, and cannulated; 12 were included in the analysis. Blood was heated in 11 pigs (one pig served as control) using a WBH device (Vithèr Hyperthermia B.V.) containing two separate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Even if it does not completely resolve the problem, the induced reduction of the virus strength induces the consequent reduction of the immunity reaction of the body. This, in turn, allows the use of many drugs which have been to show efficient but only at low virus levels [13][14][15][16][17]. We have chosen the frequency of 2.15GHZ because it is the working frequency of the microwave ovens, as it is strongly absorbed by the water.…”
Section: Description Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if it does not completely resolve the problem, the induced reduction of the virus strength induces the consequent reduction of the immunity reaction of the body. This, in turn, allows the use of many drugs which have been to show efficient but only at low virus levels [13][14][15][16][17]. We have chosen the frequency of 2.15GHZ because it is the working frequency of the microwave ovens, as it is strongly absorbed by the water.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…On this line of argument, we have proposed the idea of exploiting hyperthermia against COVID-19 to reduce the viral load and the Before going on, we must observe that a temperature increase is a strong enemy of the virus and of the Covid virus as well. In particular, it has been verified that the virulence of the covid starts to rapidly decrease when the temperature increase over 40°C [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Preliminary Remarksmentioning
confidence: 98%
See 1 more Smart Citation
“…Dewhirst et al (18) provided an exhaustive report of the time-temperature damage threshold of the human organs, having shown that animal tissues can tolerate temperature of 43-43.5°C for several hours without irreversible damage. Successive studies carried out in pigs (19) demonstrated that blood heating to 45 and 48 °C through an extracorporeal circulation device was effective in maintaining body temperature around 42-42,5 °C without major damages in organs, including brain; a sever rhabdomyolysis, which was not described by other laboratories, was, instead, observed. However, the WBHT as well as the local hyperthermia are currently used as an adjuvant therapy against many cancers, to increase the cytotoxic effect of many chemotherapeutic agents.…”
Section: The Hyperthermia and Human Organsmentioning
confidence: 96%
“…Dewhirst et al (18) provided an exhaustive report of the time-temperature damage threshold of the human organs, having shown that animal tissues can tolerate temperature of 43-43.5°C for several hours without irreversible damage. Successive studies carried out in pigs (19) demonstrated that blood heating to 45 and 48 °C through an extracorporeal circulation device was effective in maintaining body temperature around 42-42,5 °C without major damages in organs, including brain; a sever rhabdomyolysis, which was not described by other laboratories, was, instead, observed. However, the WBHT as well as the local hyperthermia are currently used as an adjuvant therapy against many cancers, to increase the cytotoxic effect of many chemotherapeutic agents.…”
Section: The Hyperthermia and Human Organsmentioning
confidence: 96%